Leadership Style and Organizational Culture as Determinants of Employee Satisfaction and Performance at PT. Karya Setiawan Ekatama - Ivany, Faya Valentia; Utami, Christina Whidya (Fakultas Ekonomi Universitas Kadiri, 2025)
Transportation is an effort to move people or goods to another place using a motorized vehicle. There has been a decrease in the number of land transportation passengers in the last 2 years. PO (Bus Company) Setiawan is a bus transportation service company that provides services for moving people/goods to another place using a motorized vehicle (KBBI, 2019). The purpose of this study is to investigate the impact of leadership style and organizational culture on employee satisfaction and performance at PT. Karya Setiawan Ekatama. The study included 92 respondents who were employees at PT. Karya Setiawan Ekatama. The survey method, which involved distributing questionnaires online via Google Forms, was used in this study to conduct sampling. The sampling method used was non-probability sampling. The results of this study indicate that leadership style and culture in the company have a significant influence on employee satisfaction and performance